Coordinated Optimization of Generator Excitation System for Improving Transmission Capacity of Power System - Guanhong WANG; Ying LI; Yao YU; Biao WANG; Xiangyu TAO; Wenfeng LI; Yong TANG (Zhongguo dianli)
For long-distance AC transmission system from energy base to load center, the system damping is insufficient when N–1 fault occurs, which leads to the reduction of transmission capacity. In order to enhance the dynamic stability of the transmission system and improve the constrained generating capacity of the generator units, the paper studies the coordinated optimization strategy of the generator excitation control system in disturbance. Aiming at above-mentioned problems, we firstly optimize the excitation system AVR main loop, the reactive current compensation and PSS parameters of generators, which reduces the lag time of generators and excitation system, decreasing the non-compensation phase frequency characteristic hysteresis by 10 degrees. And then we studies the phase compensation for PSS parameters, which brings the compensation characteristics closing to –90 degrees, substantially increasing the AC gain provided by PSS. The results show that the excitation system and PSS have important influence on the dynamic characteristics of the power grid, and under the existing parameter configuration, the delivery capacity of the power system cannot meet the full power generation requirements of generator units at the sending end. Tests have proved that under the optimized parameter configuration, the loading test results of generator units can meet the safe operation requirements of generator units and power grids, and the capacity of transmission system can be improved after N–1 fault occurs. Implementation of the optimization strategy will improve the delivery capacity of power grids for centralized power sources with high efficiency, safety and economy.